Performance Evaluation of SVD-based Digital Image Watermarking Scheme on Print-Scan and Print-Cam (PSPC) Applications - Makbol, Nasrin M.; Bee, Ee Khoo; Rassem, Taha H. (2014)
With easy and quick data distribution over the Internet, copyright protection and authentication become important applications of digital watermarking. The image watermarking schemes that are useful to serve these applications should perform well in some of challenging applications such as print-scan and print-cam (PSPC) applications. This challenge provides an impetus for research in the digital watermarking field. In this paper, the performance and the efficiency of several proposed hybrid SVD-based digital image watermarking schemes are evaluated and studied for PSPC as well as for copyright protection and authentication.